NATURE OF CODE-SWITCHING AMONG THE BANGLADESHI TERTIARY LEVEL FACEBOOK USERS - Tasnim, Zarin (PEOPLE: International Journal of Social Sciences, 2018)
The aim of this research paper to explore the different types and frequency of code switching in Facebook by the tertiary level (both graduate and undergraduate) FB users in Bangladesh. Code-switching is a regular and subconscious practice for verbal communication. But this issue is very prominent among the students of universities on the social media, especially on Facebook. I always find it interesting and so it prompted me to conduct a research study on this topic. For this purpose, a qualitative study was conducted by observing FB status updates and conversation of 10 active FB users. 4 status updates and 6 private conversations were collected as data and data were analyzed through text analysis. After data analysis, the findings show the frequency of the three types of code-switching in Facebook profiles of the tertiary level FB users. My research has revealed that university students as active FB users often switch codes in their status updates and private conversations. It has been found that all three types of code-switching namely inter-sentential, intra-sentential and tag switching occur but intra-sentential switching occurs most in their status updates and conversations. As the research was done on a very small number of participants, it cannot justify the various reasons and factors behind code-switching of the tertiary level FB users. So more studies have been recommended to find out related issues and overall impact of code-switching among the Bangladeshi young FB users.